Assessing the time required for qualitative analysis: a comparative methodological study of coding interview data in health services research = Abschätzung des Zeitaufwands qualitativer Datenanalyse : eine vergleichende methodologische Studie zur Kodierung von Interviews in der Versorgungsforschung - Ullrich, Charlotte; Wensing, Michel; Klafke, Nadja; Fleischhauer, Thomas; Brinkmöller, Sabrina; Poß-Doering, Regina; Arnold, Christine (Das Gesundheitswesen, 2025)
A reliable estimation of required resources is essential for sound research. So far, there have only been a few studies on researchers’ time investment in qualitative studies. The aim of this study, therefore, was to provide an empirical account of the estimation of timescales of qualitative analysis. In this methodological study, time expenditure was documented and compared for the focused coding of transcripts of semi-structured interviews within five qualitative studies in health services research. Data were analyzed descriptively by means of absolute frequencies. Across studies, focused coding was assessed in 94 interviews with a total interview duration of 52 hours and 44 minutes. The number of interviews per study ranged from n=11 to n=27, with a mean duration of 36 minutes. Total coding time amounted to 76 hours, with a mean of 32 min per interview. Coding time per interview time ratio ranged from 0.75 to 1.52 minutes. On average, the time spent on focused coding roughly corresponds to the duration of the interviews. Focused coding tended to get quicker over time, though variation among studies was high. The results of this study provide a reference for estimating timescales of qualitative analysis and highlights the importance of considering factors such as composition of data and researchers’ experience and involvement. In a specific research project, this effort must be balanced against the objective of the analysis, including the desired accuracy, detail and depth. Further research is needed to specify how specific parameters (i. e. nature of the study population, method of data analysis and use of concepts and theories) affect coding in qualitative analysis.
Online veröffentlicht: 14. April 2025
Gesehen am 01.10.2025